Does Surface Finishing Method Can Alter the Colour of Monolithic Zirconia Restoration? - Akan Ender; Meşe Ibrahim Talha (Balkan Stomatological Society, 2015)
Monolithic zirconia restorations offer superior mechanic properties and improve indication of non-metallic restorations. Monolithic restorations eliminate bonding and chipping problems mostly seen in zirconia restorations. However, optical properties are insufficient. Colouring or staining is offer possibility to mask the opaque view of restoration. Polishing and glazing are also surface treatment methods for monolithic zirconia.